2018
DOI: 10.1136/bcr-2017-223563
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis of the temporomandibular joint leading to an epidural abscess

Abstract: Septic arthritis of the temporomandibular joint (TMJ) is rare, but patients with this diagnosis are at high risk for significant morbidity. We present a case of a 15-year-old man who presented with increasing trismus for 3 days. He had only minimal discomfort and swelling of the right cheek and temporal region, and pericoronitis of an impacted wisdom tooth was suspected. Under intravenous antibiotics, pain subsided, but trismus and a slight swelling remained. CT scan showed septic arthritis of the TMJ with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Gayle et al has reported such unusual complication with involvement of masseteric and pterygomandibular spaces with extension to the left deep temporal region and the skull base 4. Wittig et al has reported a case of epidural abscess after septic arthritis of temporomandibular abscess which was managed by craniotomy and drainage 5. Doving et al reported cerebral abscess and Lemierre’s syndrome in a man in his early 70s and managed successfully with aggressive treatment 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gayle et al has reported such unusual complication with involvement of masseteric and pterygomandibular spaces with extension to the left deep temporal region and the skull base 4. Wittig et al has reported a case of epidural abscess after septic arthritis of temporomandibular abscess which was managed by craniotomy and drainage 5. Doving et al reported cerebral abscess and Lemierre’s syndrome in a man in his early 70s and managed successfully with aggressive treatment 6.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of these cases respond to treatment but distant spread can occur rarely depending on the general condition of the host and virulence. Unusual spread has been found in the deep neck spaces, epidural space and cerebrum 4–6…”
Section: Introductionmentioning
confidence: 99%
“…In addition to severe locoregional findings, our patient developed an intracranial abscess. Cerebral abscesses are rare complications of maxillofacial infections, including septic arthritis of the TMJ, with streptococci being the most common reported etiology [ 6 , 9 , 10 ]. Streptococci were also the offending bacterial agent in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples showed increased inflammatory markers with leucocytes at 18.8 cells per μL (3.5-10.0), sedimentation rate 58 mm (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and C-reactive protein of 251 mg/L (< 4). Platelet count was low at 98 cells per μL (145-390), and creatinine was elevated at 172 μmol/L (60-105).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation